Special Issue: Digital Truth-making: Anthropological Perspectives on Right-wing Politics and Social Media in "Post-truth" Societies - Bareither, Christoph; Harder, Alexander; Eckhardt, Dennis (Ethnologia Europaea, 2023)
How do users of social media platforms produce, shape and share truths online? In this introduction, we outline our understanding of digital truth-making as a process that builds on the affordances of digital infrastructures to entangle information with social, cultural and emotional dynamics in a way that co-constitutes beliefs and convictions about the world. The contributions to the special issue illuminate how different variations of this process can be illuminated with the help of digital ethnography and additional empirical methods. In doing so, they exemplify how digital anthropology can contribute to ongoing debates about populism and right-wing politics in “post-truth” digital societies.<br
Keywords: digital anthropology; ethnography; emotion; populism; political anthropology